Lanskap Linguistik: Kesalahan Penggunaan Bahasa Indonesia Tataran Morfologi Pada Media Publik Di Lingkungan Pendidikan Kota Surabaya - Dyas Eka Prasasti; Suhartono Suhartono (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to describe the types of morphological errors found in public media within the educational environment of Surabaya City, specifically covering the aspects of affixation, compounding, reduplication, and abbreviation. A qualitative-descriptive approach was employed. Data sources consisted of physical public media in Surabaya's educational settings such as museum information boards, directional signs, public service board, and educational displays comprising written text. Data were collected through observation, documentation, and note-taking techniques, and their validity was verified using theoretical triangulation. The study identified 96 instances of morphological errors categorized into the four aforementioned aspects. Affixation errors were the most prevalent, involving the separation of the prefix di-, failure of phoneme mutation, omission of affixes, and inconsistent affix usage. These were followed by compounding errors dominated by the incorrect writing of compound words and prolexemes as well as abbreviation errors (involving incorrect period usage and non-standard abbreviations) and reduplication errors (involving omitted hyphens and incorrect reduplicated forms). From a linguistic landscape perspective, the prevalence of these morphological errors indicates that the informational and symbolic functions of language in public spaces are not being optimally fulfilled; this potentially distorts public understanding of standard Indonesian within the educational environment.